1994
DOI: 10.1046/j.1537-2995.1994.34694295065.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of recombinant human erythropoietin to assist autologous blood donation by anemic rheumatoid arthritis patients undergoing major orthopedic surgery

Abstract: Recombinant human erythropoietin is safe and effective in stimulating erythropoiesis, allowing preoperative donation of blood for autologous use, and reducing exposure to allogeneic blood for RA patients who are unable preoperatively to deposit blood because of anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Intravenous (i.v.) iron treatment has been used to maximize the response to r-HuEPO and diminish possible r-HuEPO wastage in volunteers (Breymann et al, 1995(Breymann et al, , 1996Mercuriali et al, 1993Mercuriali et al, , 1994. The use of i.v.…”
mentioning
confidence: 99%
“…Intravenous (i.v.) iron treatment has been used to maximize the response to r-HuEPO and diminish possible r-HuEPO wastage in volunteers (Breymann et al, 1995(Breymann et al, , 1996Mercuriali et al, 1993Mercuriali et al, , 1994. The use of i.v.…”
mentioning
confidence: 99%
“…The erythropoietic response was evaluated by the difference between baseline and end of treatment hemoglobin levels and by the production of new RBC (RBC gain) according to Mercuriali et al [9]. …”
Section: Methodsmentioning
confidence: 99%
“…Preoperative treatment with recombinant human erythropoietin (r–HuEPO) enhanced erythropoiesis, increased autologous blood collection and reduced perioperative transfusions in anemic patients with gastrointestinal cancer or rheumatoid arthritis [7, 8, 9]. One drawback of this therapy is the high cost, which limits a wide application.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of epoetin alfa in patients undergoing major elective orthopaedic surgery has been demonstrated in numerous clinical studies (Table 2) [1,4,5,7,11,15,16,17,18,21,22,26,32,33,40,41,42]. These studies established the clinical rationale, the optimum dosage regimen, and identified orthopaedic patient populations that demonstrated significant benefits from epoetin alfa treatment [4,7,11,15].…”
Section: Clinical Rationale For Perioperative Epoetin Alfamentioning
confidence: 99%